Individualist-collectivist construct and the social aspects of shopping. - Ng, Siu Fang. (2008)
The paper seeks to explain the attitudes of young Singaporean adults toward online shopping and real life shopping. It examines the impact of the individualist-collectivist construct on shopping behaviour in Singapore. In addition, it discusses alternative factors that influence the shopping behaviour.